CAR T cells – the future for cancer therapy. (May 2021) - Benjamin, Reuben
Abstract: Chimeric antigen receptor T (CAR T) cells are a novel form of immunotherapy in which T cells from patients with cancer are genetically modified to express a chimeric receptor enabling them to target cancer cells, with profound anti-tumour effects. CAR T cells have shown highly impressive results in the treatment of B cell haematological malignancies, with several CD19-targeted CAR T products now approved for routine clinical use. The main adverse effects of CAR T cell treatment include cytokine release syndrome, neurotoxicity and cytopenias; these require prompt treatment in specialist centres. Future developments in the CAR T field are likely to see products with improved efficacy, a greater range of cancers being treated and more affordable and easier access to this promising therapy.